Perspektif keadilan dalam kontrak komersial berdasarkan asas proporsionalitas: analisis normatif terhadap praktik hukum kontrak di Indonesia - Lisza Nurchayatie; Taufik Efendi; Handoyo Prasetyo (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Commercial contract practices in Indonesia still reveal an imbalance of bargaining power, particularly through the use of standard-form contracts that often disadvantage one party. This condition raises questions regarding the role of the principle of proportionality in achieving contractual justice. This study aims to analyze the application of the proportionality principle as a corrective instrument to the freedom of contract in order to realize a fair balance of rights and obligations between parties. This research employs a normative legal method using statutory, conceptual, case, and comparative approaches, based on primary legal materials such as the Indonesian Civil Code and court decisions, as well as relevant national and international literature on contractual fairness. The findings indicate that the proportionality principle plays a vital role in maintaining substantial balance between contracting parties and aligns with Aristotle’s theories of distributive and corrective justice. However, its implementation remains weak due to the lack of control over standard contract clauses. The study recommends adopting the proportionality principle as a benchmark for contract formulation and judicial review to ensure fair, ethical, and sustainable business practices.